Endoscopic diagnostics in colorectal carcinoma - Gil, Jerzy; Wojtuń, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2006)
Increacing incidence of colorectal carcinoma in polish population demands development of new endoscopic diagnostic methods as well as improvement of existing ones. The most important factor influencing the treatment result is early detection of colorectal cancer as well as pre malignant lesions thus diagnostics of non-symptomatic patients is so important. Early detection of lesions is a greater survival chance for patient as well as a source of satisfaction for physician. The method used for achieving such result is a screening colonoscopy. It is connected with treatment procedures. The development of this method of diagnostic increased the rate of diagnosed colorectal cancer. The significant increase of proper diagnosis establishing in colonoscopy could be achieved by use of chromoscopy and magnifying methods and polypectomy. Nowadays the further increase of diagnostic accuracy as well as rate of complete recovery could be achieved thanks to the identification of flat adenomas. Mucosectomy is here a method of choice. Despite diagnostic methods development the basis of endoscopic methods is a proper macroscopic evaluation of mucosa and histopathological assessment of found lesions. Endosonography plays an important role in preoperative staging of colorectal carcinoma. This could influence a choice of method of curative procedure. Colonoscopy is a basic diagnostic method used in oncological surveillance in patients with colorectal cancer or with premalignant lesions previously endoscopically or surgically treated.